2014
DOI: 10.2319/072214-510.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of real and ideal wire-slot play in square and rectangular archwires

Abstract: Objective: To evaluate the degree to which the height, width, and cross-section of rectangular and square orthodontic archwires affect the play between the archwires and the bracket slot. Materials and Methods: The stated measurements (height and width) of 43 archwires from six different manufacturers were compared with real values obtained using a digital gauge. The curvature (radius) of the edge bevels was also measured to calculate the play within the slot, and this measurement was compared with the ideal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 13 publications
2
22
0
5
Order By: Relevance
“…A possible explanation for this difference in frictional resistance was the disparity in wire-bracket slot play. As the heights, widths, and cross sections of rectangular orthodontic wires affect the play between the wires and the bracket slot, 19 the degrees of play of 0.016-inch round and 0.016 3 0.022-inch and 0.017 3 0.025-inch rectangular wires in the 0.018-inch slots can be assumed to be greater than those of 0.018inch round and 0.017 3 0.025-inch and 0.019 3 0.025inch rectangular wires in a 0.022-inch slot.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this difference in frictional resistance was the disparity in wire-bracket slot play. As the heights, widths, and cross sections of rectangular orthodontic wires affect the play between the wires and the bracket slot, 19 the degrees of play of 0.016-inch round and 0.016 3 0.022-inch and 0.017 3 0.025-inch rectangular wires in the 0.018-inch slots can be assumed to be greater than those of 0.018inch round and 0.017 3 0.025-inch and 0.019 3 0.025inch rectangular wires in a 0.022-inch slot.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the real height and width of the archwires differed from those stated by the manufacturers. 7 The present study was done to compare the archwire dimensions between three different companies (Modern Orthodontics, Prime orthodontics and Captain Orthodontics and compare the dimensions with the standard value published by the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“…A expressão do torque está diretamente ligada as variações estruturais que podem ser encontradas nos bráquetes (dimensões e forma das canaletas, e material de fabricação), e nas variações dimensionais e estruturais dos fios ortodônticos (Badawi et al, 2008;Archambault et al, 2010;Major et al, 2011;Streva et al, 2011;Franco et al, 2015;Lombardo et al, 2015;Lee et al, 2016). provavelmente porque em 12º, e em 24º o momento de torque ocorreu dentro do limite, ou muito próximo ao valor mensurado da folga nos bráquetes H4.…”
Section: Discussionunclassified
“…Outro fator relevante a ser mencionado é que os resultados obtidos nessa pesquisa podem apresentar diferenças nos valores nominais quando comparados a outros estudos (Badawi et al, 2008;Archambault et al, 2010;Franco et al, 2015), pelo fato do fio de aço inóxidável apresentar diferenças em sua propriedade e composição estrutural, em diferentes marcas comerciais (Gioka;Eliades, 2004;Vena et al, 2007;Lombardo et al, 2015).…”
Section: Discussionunclassified
See 1 more Smart Citation